BELAJAR SISWA MENGGUNAKAN PEMBELAJARAN ACTION LEARNING DENGAN POKOK BAHASAN MAKNA BERIMAN KEPADA QADHA DAN QODHAR PADA SISWA KELAS XII MIPA SMA NEGERI 2 LUBUK PAKAMTAHUN PELAJARAN 2019/2020 - Latifah Hanum (Jurnal Guru Kita PGSD, 2021)
Abstract: Student Learning Using Action Learning Learning with the Subject of the Meaning of Faith in Qadha and Qodhar in Class Xii Mipa Students of Sma Negeri 2 Lubuk Pakam for the 2019/2020 Academic Year. To improve student learning achievement, learning action learning is one of the learning activities that can help students to more easily understand the material to be studied. In the learning process, the action learning model aims to make it easier for teachers in the process of delivering subject matter to be more effective and efficient. Besides being able to motivate students, the use of action learning learning models can also make it easier for students to understand and absorb the subject matter. The application of action learning learning is very suitable to be applied to Islamic religious education lessons this is because the form of creative learning learning places more emphasis on critical and innovative thinking processes. Keywords: Action Learning, Qadha and Qodhar Abstrak: Belajar Siswa Menggunakan Pembelajaran Action Learning Dengan Pokok Bahasan Makna Beriman Kepada Qadha Dan Qodhar Pada Siswa Kelas Xii Mipa Sma Negeri 2 Lubuk Pakamtahun Pelajaran 2019/2020. Untuk meningkatkan Prestasi beljar siswa, pembelajaran action learning merupakan salah satu kegiatan pembelajaran yang dapat membantu siswa untuk lebih mudah dalam memahami materi yang akan dipelajari. Dalam proses pembelajaran model pembelajaran action learning bertujuan untuk mempermudah guru dalam proses penyampaian materi pelajaran agar lebih efektif dan efisien. Selain dapat memberikan motivasi kepada siswa, penggunaan model pembelajaran action learning dapat juga mempermudah siswa dalam memahami dan menyerap materi pelajaran. Penerapan pembelajaran action learning sangat sesuai diterapkan pada pelajaran pendidikan agam Islam hal ini disebabkan karena bentuk pembelajaran creative learning lebih menekankan pada proses berfikir kritis dan inovatif. Kata kunci : Action Learning,  Qadha  dan Qodhar